2011
DOI: 10.1037/a0023441
|View full text |Cite
|
Sign up to set email alerts
|

Play therapy outcome prediction: An exploratory study at a university-based clinic.

Abstract: In this study we investigated the prediction of child centered play therapy (CCPT)/nondirective play therapy on emotional and behavioral problems using archival data from 82 child clients at a university-based counseling clinic. Statistically significant predictions were found on the Internalizing and Externalizing Problems scales on the Child Behavior Checklist. Termination and family relationship concerns variables were found to be strong contributors to predicting greater improvement. Results are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This approach is based on Carl Rogers’s person-centered theory. Research published in the last decade using CCPT has been found to be effective at improving children’s academic achievement (Blanco & Ray, 2011; Blanco, Ray, & Holliman, 2012), reducing externalizing behaviors (Bratton et al, 2013; Dougherty & Ray, 2007; Muro, Ray, Schottelkorb, Smith, & Blanco, 2006; Ray, 2007, 2008; Ray, Blanco, Sullivan, & Holliman, 2009; Ray, Henson, Schottelkorb, Brown, & Muro, 2008; Schottelkorb & Ray, 2009; Schottelkorb, Swan, Jahn, Haas, & Hacker, 2015; Schumann, 2010; Tsai & Ray, 2011), reducing internalizing behaviors (Baggerly & Jenkins, 2009; Cheng & Tsai, 2014; Muro et al, 2006; Ray, 2008; Ray, Stulmaker, Lee, & Silverman, 2013; Stulmaker & Ray, 2015; Tsai & Ray, 2011), improving teacher–child relationship (Ray, 2007; Ray et al, 2008), reducing trauma symptoms (Schottelkorb, Doumas, & Garcia, 2012), reduction in somatization (Schottelkorb et al, 2015), and improvement in functioning for children with developmental delays or intellectual disabilities (Garofano-Brown, 2012; Swan & Ray, 2014; Ware Balch & Ray, 2015).…”
mentioning
confidence: 99%
“…This approach is based on Carl Rogers’s person-centered theory. Research published in the last decade using CCPT has been found to be effective at improving children’s academic achievement (Blanco & Ray, 2011; Blanco, Ray, & Holliman, 2012), reducing externalizing behaviors (Bratton et al, 2013; Dougherty & Ray, 2007; Muro, Ray, Schottelkorb, Smith, & Blanco, 2006; Ray, 2007, 2008; Ray, Blanco, Sullivan, & Holliman, 2009; Ray, Henson, Schottelkorb, Brown, & Muro, 2008; Schottelkorb & Ray, 2009; Schottelkorb, Swan, Jahn, Haas, & Hacker, 2015; Schumann, 2010; Tsai & Ray, 2011), reducing internalizing behaviors (Baggerly & Jenkins, 2009; Cheng & Tsai, 2014; Muro et al, 2006; Ray, 2008; Ray, Stulmaker, Lee, & Silverman, 2013; Stulmaker & Ray, 2015; Tsai & Ray, 2011), improving teacher–child relationship (Ray, 2007; Ray et al, 2008), reducing trauma symptoms (Schottelkorb, Doumas, & Garcia, 2012), reduction in somatization (Schottelkorb et al, 2015), and improvement in functioning for children with developmental delays or intellectual disabilities (Garofano-Brown, 2012; Swan & Ray, 2014; Ware Balch & Ray, 2015).…”
mentioning
confidence: 99%
“…Some studies have highlighted a range of potential individual-level predictors of poorer outcomes, such as comorbidity (Liber et al, 2010) and younger age (Weisz, Weiss, Han, Granger & Morton, 1995). Concomitantly, better outcomes have been associated with particular kinds of initial problems, such as family relationships or behavioural problems (Tsai & Ray, 2011), low parental level of education and the presence of both parents in family (Gardner et al, 2009), older age and disability (Cooper, Stewart, Bunting & Sparks, 2013). School-level predictors, on the other hand, although identified as a promising area of research (Fox & Butler, 2009), have not been explored so far.…”
mentioning
confidence: 99%
“…In accordance with this research, the U.S. Public Health Service () called for the development, research, and use of family‐centered approaches to promote children's mental health; however, there appears to be a lack of practitioners who are using such interventions, especially with families with young children. Family therapists and play therapists are two groups of professionals in particular who have frequent contact with this population (Doherty & Simmons, ; Hines, ; Kranz, Kottman, & Lund, ; Ryan, Gomory, & Lacasse, ; Tsai & Ray, ); however, practitioners within these areas have voiced concerns regarding the lack of inclusive family treatment (Haslam & Harris, ; Miller & McLeod, ; Sori & Sprenkle, ).…”
Section: Examining the Impact Of Child Parent Relationship Therapy (Cmentioning
confidence: 99%